Prevalence and correlates of anger among undergraduate students in Malaysia - Tusimin, Maiza; Mamat @ Mukhtar, Firdaus; Wong, Shi Yie; Abd Razak, Muhammad Hariz (Innovative Journal, 2018)
Anger is a vital emotion for human survival. Mild level of anger that occurs briefly can be beneficial, but it may cause harm if it occurs continuously with poor control. Specifically, among medical doctors, controlling emotion is important to keep check of their professional conduct. In Malaysia, there is a growing number of reports on the misconduct and aggressive behaviours of health care workers, including housemen and medical doctors, proving a need to explore the issue among current medical trainees. Hence, this study aims to investigate the association between socio-demographic characteristics with anger among medical students in the Universiti Putra Malaysia. Cross-sectional study with stratified random sampling method was conducted. Novaco Anger Inventory and the State and Trait Anger Expression Inventory-2, was used in current study. The results showed a significant association between gender (p= 0.015) and intensity of anger. Besides, results also showed a significant association between gender and trait anger levels (p=0.003). For anger expression and control, the results showed a significant associations between year of study (p= 0.028) and gender (p=0.015), with anger expression and control. There was a relationship between year of study and anger expression, as well as gender and intensity of anger, trait anger levels, and anger expression.